Observing the Social World: Doing Qualitative Sociology - Osnowitz, Debra (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In this course, we will make the researcher's questions and strategies our central focus,asking what the researcher observed and how the researcher used observations todevelop an analysis of some aspect of social life. To deduce research strategies, we will,in a sense, work backwards as we read published studies. Looking at sources, at the fitbetween evidence and analysis, we will consider the construction of qualitative sociologyas a process of decision making. To cast a wide net during a single semester, we willread excerpts from longer studies, along with reflective writing about doing research. Wewill also analyze visual media, including film, which differ from written texts in theirrepresentation of the social world and can provide both sensory data and an additional dimension for analysis.